Experimental investigation of heat transfer in a triple tube heat exchanger with coiled spring inserts. Issue 5 (18th February 2021) - Kumar, Rajan; Chandra, Prakash
Abstract: Experiments have been performed to investigate the effect of coiled spring inserts on heat transfer, pressure drop, and performance parameters of a triple tube heat exchanger (TTHX). Three different spring inserts having a pitch of 5, 10, and 15 mm are used and the diameter of the spring wire is taken as 1 mm. The experiments were carried out under a turbulent flow regime, with water as a working medium in parallel and counter flow configurations. The variation in different performance characteristics like heat transfer coefficient, Nusselt number, and effectiveness have been compared at various Reynolds numbers ranging between 4000 and 16, 000 in the considered flow patterns. The Nusselt number of TTHX with the lowest pitch spring is found to be higher than that of the plain TTHX by 57.27% at Re  = 4000 for the counter flow configuration. Both the thermal performance factor and effectiveness increased as the pitch of the spring insert was decreased. The effectiveness of TTHX with the lowest pitch spring insert is found higher than that of the plain TTHX by 43.84% in the counter flow pattern.